PENGARUH PENERAPAN PELAYANAN ANC BIDAN DENGAN LAYANAN 5S TERHADAP KEPUASAN IBU HAMIL DI PUSKESMAS HARUAI - Esterlina, Maria; Suhartati, Susanti; Rizali, Muhammad (LPPM Universitas Sari Mulia, 2023)
Background: Satisfaction-oriented health services, especially ANC services with 5S services. Satisfaction can affect interest in returning, if the patient is satisfied it will have a positive impact on the puskesmas. Many implementations of 5S in providing services for pregnant women have not been maximized Objective: It is known how the influence of implementing midwifery services with 5S services on the satisfaction of pregnant women at the Haruai Health Center. Methods: This research uses quantitative observational with a cross- sectional approach. The research population is 75 people. The sample uses non-probability sampling accidental sampling. Results: in this study, the p value = 0.075 > α 0.05, which means that there is no effect of the implementation of ANC midwives services with 5S services on the satisfaction of pregnant women at the Haruai Health Center. Conclusion: Most midwives (93.7%) have implemented 5S when providing midwifery services. However, there are still a small number of midwives who do not implement 5S services, namely as many as 6.3%. Most of the pregnant women 87.3% were satisfied with the services that had been provided and a small portion were dissatisfied as much as 12.7%. And from the results of the Chi=Square test, it was found that p value = 0.075 > α 0.05, which means that there is no effect of the implementation of the Midwife's 5S services on the satisfaction of pregnant women at the Haruai Health Center. Keywords: Pregnant Women, 5S, Satisfaction